Simvastatin therapy in elderly patients with chronic heart failure: potential cardiodepressive effects - A. L. Pirogov; T. I. Vlasova (Кардиоваскулярная терапия и профилактика)
Aim. To study the effects of simvastatin (20 mg/d) on cardiac hemodynamics and chronic heart failure (CHF) clinical course in elderly patients.Material and methods. The study included 180 elderly patients (mean age 80,8±5,8 years) with Functional Class (FC) II-III CHF, left ventricular (LV) systolic and diastolic dysfunction. All participants were divided into 2 equally sized groups, receiving standard CHF treatment, or standard treatment plus simvastatin (20 mg/d). The follow-up period lasted for 12 months, with intermediate control assessment after 3 months of the treatment. Clinical status, Doppler echocardiography, lipid profile parameters, and tumor necrosis factor-alpha (TNF-alpha) level were controlled. End-points included CHF death or any acute vascular event.Results. Starting from the first month of the treatment, there was a significant difference in end-point number (р=0,028), CHF FC (p<0,001), angina FC (р<0,0001) and TNF-alpha level (p<0,05). Simvastatin therapy was not associated with reduced LV pump function.